Phylogenetic analysis of the grouper family (Serranidae) from various local markets in Indonesian waters using COI (cytochrome oxidase I) - Tomi Apra Santosa; Winda Ayu Fietri; Abdul Razak; Ramadhan Sumarmin (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
Grouper fish (Serranidae) is a type of fish found in Indonesian waters. However, not many people have conducted further research on phylogenetics based on COI (Cytochrome Oxidase I). This study aims to explain the phylogeny of grouper fish from the Serranidae family based on COI (Cytochrome Oxidase I). This research is a literature study. The research samples were grouper fish from Lombok, Karimunjawa, Lampung, Kendari, Madura, Tanakeke, and Numfor. The research instrument was a grouper-type observation sheet and an observation sheet for the results of the MEGA 7 application test. The data were analyzed using qualitative descriptive analysis. The results showed that the level of kinship between the species tested was very close, including Epinephelus areolatus, E. merra, E. fasciatus, E. longispinis, E. coioides, E. ongus, and E. coeruleopunctatus with all genetic distance averages type. 0.02. The conclusion of this study is that in general the species relationships found are several species found in the same location with similar morphology and diet.